Olivia plants a garden - Sollinger, Emily; Osterhold, Jared (New York : Simon Spotlight, 2011)
When Olivia's teacher gives Olivia a "surprise" plant seed envelope, she takes care of the seed in her garden, excited to discover what kind of plant she will grow.
"As seen on Nickelodeon"--Jacket.
Includes bibliographical references and index.
Keywords: Gardening -- Fiction; Gardens -- Fiction; Swine -- Fiction; Olivia (Fictitious character : Falconer) -- Juvenile fiction; Gardening -- Juvenile fiction; Gardens -- Juvenile fiction; Swine -- Juvenile fiction; Gardening -- Fiction; Gardens -- Fiction; Pigs -- Fiction; Rebuses